Accuracy of two methods to detect the presence of halitosis: the volatile sulfur compounds concentration in the mouth air and the information from a close person - Nádia Cristina Pinheiro RODRIGUES; Alexandre ABRÃO NETO; Paulo NADANOVSKY (University of São Paulo, 2023)
Abstract This study aimed to analyze the accuracy of two methods for detecting halitosis, the organoleptic assessment by a trained professional (OA) with volatile sulfur compounds (VSC) measurement via Halimeter® (Interscan Corporation) and information obtained from a close person (ICP). Methodolody Participants were patients and companions who visited a university hospital over one year period to perform digestive endoscopy. A total of 138 participants were included in the VSC test, whose 115 were also included in the ICP test. ROC curves were constructed to establish the best VSC cut-off points. Results The prevalence of halitosis was 12% (95%CI: 7% to 18%) and 9% (95%CI 3% to 14%) for the OA and ICP, respectively. At the cut-off point >80 parts per billion (ppb) VSC, the prevalence of halitosis was 18% (95%CI: 12% to 25%). At the cut-off point >65 ppb VSC, sensitivity and specificity were 94% and 76%, respectively. At the cut-off point >140 ppb, sensitivity was 47% and specificity 96%. For the ICP, sensitivity was 14% and specificity 92%. Conclusions VSC presents high sensitivity at the cut-off point of >65 ppb and high specificity at the cut-off point of >140 ppb. ICP had high specificity, but low sensitivity. The OA can express either occasional or chronic bad breath, whereas the ICP can be a potential instrument to detect chronic halitosis.